PENGARUH LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DI INDONESIA - Rejeki, Halim Tri; Haryono, Slamet (Invoice : Jurnal Ilmu Akuntansi, 2021)
This study aims to examine the effect of leverage and company size on firm value, which in this study uses the Price to Book Value (PBV) measure which is a ratio that indicates whether the valuation is overvalued (above or below the valuation (below the book value of shares is the stock price can be traded) Firm value is one of the indicators of company performance appraisal in general. In addition, company value is also a consideration for investors who will invest. The population in this study is the mining and agricultural sub-sector companies listed on the Indonesia Stock Exchange. (BEI) 2013-2018. The sampling technique used purposive sampling, namely the selection of samples based on certain criteria according to what the researchers wanted. The number of samples used in this study were 7 (seven) companies with six years of observation, so that 42 data were selected. observation.Data used is secondary data in the form of the company's annual financial statements obtained from the Indonesia Stock Exchange (IDX). The data analysis technique in this research is descriptive statistics and panel data analysis. The software used for data processing is Eviews 2010 and excel. The test results show that, only the leverage variable has an effect and is in accordance with the theory, this is because the company data used has a large difference in total assets.Keywords: Price to Book Value, Firm Value, Leverage, Company Size